The Impact of Electronic Word of Mouth (e-WOM) on Consumer’s Purchase Intention towards Local Skincare Brand with Brand Image as The Mediator: A Case of Somethinc - Devina Nathania; Livia Anabel Foek (iBuss Management, 2023)
With the increasing trend of online shopping and the emerging local skincare industry in Indonesia, the internet has been connecting consumers with the local skincare brands and stimulating their intention to purchase. The objective of this study was to further analyze the impact of electronic word of mouth (e-WOM) in shaping the image of a brand which then impacts consumer purchase intention towards local skincare brands. Somethinc was the subject of this study since the brand has become one of the fastest-growing local skincare brands in Indonesia. Using random sampling from the probability sampling method, the online survey of this study involved participants who are Indonesian-born and residents aged 19 to 45 years old and are aware of Somethinc’s brand existence on any platform on the internet. The data gathered were analyzed and tested upon the hypothesis using the PLS-SEM method. The result suggested that brand image significantly mediates the relationship between e-WOM and purchase intention, in which e-WOM establishes how consumers perceive the brand image of Somethinc, which subsequently increases their intention to purchase Somethinc’s products. Through this understanding, local skincare brands in Indonesia, Somethinc specifically, will benefit from the result of this study to further improve their strategy and retain more consumers. Keywords: e-WOM, purchase intention, brand image, local skincare brand, Somethinc, online reviews, online recommendations, online platform, social media.